Proteic and phenolics compounds contents in Bacupari callus cultured with glutamine and nitrogen sources - Marques,H. P. (2018)
Abstract In this study was evaluated the influence of glutamine supplementation on the endogenous content of amino acids, proteins, total phenolics, flavonoids and proanthocyanidins in Bacupari callus. The explants were inoculated in MS medium, MS with half concentration of the nitrogen salts (MS½) and nitrogen-free MS, supplemented with glutamine (5, 10, 30 and 60mM) named as Gln5, Gln10, Gln30 and Gln60. Amino acids and proteins were analyzed after 20, 80 and 140 days and the secondary metabolites on the 140th day. There was no difference in the amino acids on the 20th day. On the 80th day the treatments MS and MS½ presented the lowest levels. On the 140th day MS and MS½ presented the lowest amino acid concentration and Gln10 the highest. Concerning proteins, there was difference only on the 140th day, being the highest concentrations observed in Gln5, and the lowest in MS½ treatment. Total phenolics content was higher in the treatment Gln60 and lowest in MS. Treatments Gln5, Gln10, Gln30 and MS½ were statistically equal. For flavonoids, the highest values occurred in the treatments Gln30, Gln60 and MS½ and the lowest in Gln5, Gln10 and MS. Similarly, for the proanthocyanidins the highest concentrations were observed in treatment Gln60 and the lowest in Gln5 and MS. In conclusion, the treatment with 60mM of glutamine favors the protein accumulation and production of secondary metabolites in Bacupari callus.